An electrocatalyst capable of controlling the crystallinity of MoO2 and its preparation method and application
By using low crystallinity or amorphous MoO2 hollow nanospheres supported by ruthenium atoms, the existing electrodes have few active sites and poor conductivity, and efficient and stable electrocatalytic hydrogen evolution performance is achieved, and the preparation cost is reduced.
Patent Information
- Application Number
- CN202411947580.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-04-08
AI Technical Summary
The existing transition metal oxide electrodes have few active sites, poor conductivity, high preparation cost and poor catalytic effect.
The low-crystalline or amorphous MoO2 hollow nanospheres were used as support to support the electrocatalyst to form a heterostructure, and the crystallinity of MoO2 was adjusted by NaBH4 treatment.
The dispersion of ruthenium atoms of the catalyst particles and the exposure of active sites are improved, the electrocatalytic hydrogen evolution performance is enhanced, the preparation cost is reduced, and the stability of the catalyst is significantly improved.
Smart Images

Figure CN119776880A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of electrocatalytic materials, and in particular relates to an electrocatalyst capable of controlling and adjusting the crystallinity of MoO2, and a preparation method and application thereof. Background Art
[0002] Hydrogen plays a key role in future energy conversion and storage due to its high energy density. Producing green hydrogen by using renewable energy for water electrolysis provides a feasible way to reduce environmental pollution caused by fossil fuel consumption. Alkaline electrolysis has attracted attention as a promising and sustainable large-scale hydrogen production technology due to its low-cost catalysts. Currently, platinum-based materials are the most active known hydrogen evolution reaction (HER) catalysts, but their high cost and scarcity limit their widespread application. Therefore, it has become particularly urgent to find alternative catalysts with high activity and low cost.
[0003] Ruthenium (Ru) is comparable to platinum (Pt) in hydrogen bond strength and has a much lower cost than Pt, making Ru-based catalysts a potential replacement for scarce Pt-based catalysts. Currently, researchers have proposed a variety of methods to optimize Ru-based catalysts. Among them, electron metal-support interaction (EMSI) has received extensive attention in the past few decades as an effective means to regulate the catalytic performance of various reactions. EMSI is characterized by charge transfer and orbital reorganization at the interface between metal and support materials, which leads to the formation of new chemical bonds and the redistribution of molecular energy levels. EMSI-induced electron transfer further adjusts the d-band center of metal nanocatalysts, reduces the adsorption and desorption energy barriers of reaction intermediates, and thus accelerates the catalytic reaction. Among the many support materials, low-cost metal oxides are widely used due to their advantages such as easy synthesis, good stability, and easy anchoring of heteroatoms, but their high resistivity limits the effective transfer of electrons, resulting in reduced activity.
[0004] Therefore, the development of a mild, simple, efficient, controllable, high-performance, high-quality, active, crystallinity-adjustable transition metal oxide-loaded metal nanomaterial composite catalyst and its green chemical preparation method is of great significance to promoting the process of hydrogen production by water electrolysis. Summary of the invention
[0005] The present invention aims to at least solve the problems of the existing transition metal oxide electrodes, such as the small number of active sites, poor conductivity, high preparation cost and poor catalytic effect. To this end, the present invention proposes an electrocatalyst with controllable MoO2 crystallinity and a preparation method and application thereof, wherein the electrocatalyst has a heterogeneous structure of low-crystallinity or amorphous MoO2 hollow nanospheres loaded with ruthenium atoms, and is applied to the alkaline water electrolysis hydrogen production reaction, which not only exhibits excellent catalytic activity, but also has high stability, and is expected to be applied to industrial large-scale water electrolysis hydrogen production.
[0006] To solve the above technical problems, the first aspect of the present invention provides an electrocatalyst, including a carrier and ruthenium atoms, wherein the ruthenium atoms are loaded on the surface of the carrier and form a heterostructure therewith; the carrier is low-crystallinity or amorphous MoO2 hollow nanospheres.
[0007] It should be pointed out that the low crystallinity mentioned in the present invention refers to the atomic arrangement containing some short-range disorder in the crystal structure, and the amorphous state refers to the amorphous or glassy state.
[0008] Specifically, the catalyst of the present invention uses low-crystallinity or amorphous MoO2 hollow nanospheres as carriers, which, on the one hand, is beneficial to improving the dispersion of ruthenium atoms in catalyst particles on the surface of the MoO2 hollow nanospheres, so that the active sites are fully exposed and utilized, thereby improving the electrocatalytic hydrogen evolution performance; on the other hand, the low-crystallinity or amorphous MoO2 structure containing some short-range disordered atomic arrangements will cause huge structural distortion and unsaturated coordinated atoms relative to high-crystallinity MoO2 crystals, thereby improving the electronic structure of the material and further enhancing the electrocatalytic hydrogen evolution performance of the material.
[0009] In some embodiments of the present invention, the crystallinity of the MoO2 is less than 23%, that is, the crystallinity of the MoO2 can be 0-23%, such as 0%, 19.6%, 22.8%, etc. When the crystallinity of MoO2 is 0%, it is amorphous.
[0010] In some embodiments of the present invention, the loading amount of ruthenium atoms is less than 5wt%. The loading amount of ruthenium in the electrocatalyst of the present invention is lower than the loading amount of metal atoms in commercially available precious metal electrocatalysts (such as Pt / C, the loading amount of Pt is 20wt%; Ru / C, the loading amount of Ru is 5wt%), and the electrocatalytic performance is better, and has a broader application prospect.
[0011] The second aspect of the present invention provides a method for preparing the above-mentioned electrocatalyst, comprising the following steps:
[0012] (1) dissolving molybdate in water, adding dopamine hydrochloride and ethanol, mixing, and adjusting the pH value of the solution to be alkaline to obtain a mixed solution;
[0013] (2) adding a ruthenium source to the mixed solution and mixing; centrifuging and drying to obtain a precursor powder;
[0014] (3) annealing the precursor powder in an inert atmosphere to obtain high-crystallinity MoO2 hollow nanospheres loaded with ruthenium atoms, denoted as Ru / -C-MoO2;
[0015] (4) The Ru / -C-MoO2 is dissolved in water, NaBH4 is added to adjust the crystallinity, and after centrifugation and drying, low-crystallinity or amorphous MoO2 hollow nanospheres loaded with ruthenium atoms are obtained, which are recorded as Ru / -AC-MoO2 or Ru / -A-MoO2.
[0016] Specifically, when preparing the electrocatalyst of the present invention, firstly, a ruthenium (Ru)-modified Mo-polydopamine hollow framework is self-assembled by polymerization induction in an alkaline solution at room temperature, and then annealed at high temperature to form a high-crystallinity MoO2 hollow nanosphere Ru / -C-MoO2 loaded with ruthenium atoms, and then treated with a strong reducing agent NaBH4 to reduce the high-valent MoO2 to a low-valent MoO 2-x At the same time, H extracts O atoms in the lattice, resulting in the formation of O vacancies accompanied by H oxidation, reduction of metal form and reduction of crystallinity, thereby forming low-crystallinity or amorphous MoO2 hollow nanospheres Ru / -AC-MoO2 or Ru / -A-MoO2 loaded with ruthenium atoms. The formation of this low-crystallinity structure containing some short-range disordered atomic arrangements will cause huge structural distortion and unsaturated coordinated atoms, thereby improving the electronic structure of the material and enhancing the electrocatalytic hydrogen evolution performance of the electrocatalyst.
[0017] In some embodiments of the present invention, in step (1), the molybdate is selected from ammonium molybdate tetrahydrate and / or sodium molybdate.
[0018] In some embodiments of the present invention, in step (1), the molar ratio of Mo ions in the molybdate to dopamine hydrochloride is 1:(1-3).
[0019] In some embodiments of the present invention, in step (1), the pH value is 8.5-10.2, which can be adjusted by adding ammonia water.
[0020] In some embodiments of the present invention, in step (1), the volume ratio of water to ethanol is 1:(1-4).
[0021] In some embodiments of the present invention, in step (2), the ruthenium source is selected from one of ruthenium dichloride, ruthenium trichloride, ruthenium oxalate, ruthenium nitrate, and ruthenium acetylacetonate.
[0022] In some embodiments of the present invention, in step (2), the usage ratio of the molybdate and the ruthenium source is 1:(5-40) in terms of the molar ratio of Ru to Mo.
[0023] In some embodiments of the present invention, in step (3), the temperature regime of the annealing treatment is: heating to 450-850°C at a rate of 1-10°C / min for annealing for 2-6 hours, and then cooling to room temperature.
[0024] In some embodiments of the present invention, in step (3), the inert atmosphere is a nitrogen atmosphere or an argon atmosphere.
[0025] In some embodiments of the present invention, in step (4), the mass ratio of Ru / -C-MoO2 to NaBH4 is 1:(1-4).
[0026] In some embodiments of the present invention, in step (4), the centrifugation further includes washing 3-5 times with deionized water and anhydrous ethanol.
[0027] In some embodiments of the present invention, in step (4), the drying temperature is 50-130°C.
[0028] In some embodiments of the present invention, in step (4), the drying time is 3-24 hours.
[0029] The third aspect of the present invention provides use of the above electrocatalyst in electrocatalytic hydrogen evolution.
[0030] In some embodiments of the present invention, the application is to produce hydrogen by alkaline water electrolysis.
[0031] Compared with the prior art, the above technical solution of the present invention has at least the following technical effects or advantages:
[0032] (1) The electrocatalyst of the present invention includes a carrier with low crystallinity or amorphous MoO2 hollow nanospheres as the carrier, and ruthenium atoms are loaded on the surface of the carrier to form a heterogeneous structure with the carrier. The MoO2 hollow nanospheres are beneficial to improving the dispersion of ruthenium atoms on the surface of the catalyst particles, so that the active sites are fully exposed and utilized, and the electrocatalytic hydrogen evolution performance is improved; the low crystallinity or amorphous MoO2 structure, relative to the high crystallinity MoO2 crystal, will cause huge structural distortion and unsaturated coordinated atoms, thereby improving the electronic structure of the material and further enhancing the electrocatalytic hydrogen evolution performance of the material.
[0033] (2) When preparing the electrocatalyst of the present invention, MoO2 hollow nanospheres are synthesized by room temperature self-assembly, and ruthenium atoms are loaded on the MoO2 hollow nanospheres, which effectively improves the dispersion of catalyst particles on their surface, which is beneficial to the exposure and full utilization of active sites; at the same time, the crystallinity of the MoO2 carrier can be controlled and adjusted at room temperature by using NaBH4, and the inherent activity of the material can be enhanced in multiple dimensions by adjusting the degree of amorphization of the carrier. This method of enhancing the carrier by controlling the adjustment of transition metal oxides at room temperature provides a new direction for the efficient and controllable synthesis of catalyst carriers with different crystallinities.
[0034] (3) The present invention uses low-crystallinity or amorphous transition metal oxide MoO2 hollow nanospheres loaded with ruthenium atoms in a heterogeneous structure, which greatly reduces the amount of precious metals used in the preparation process compared to commercial Ru / C and Pt / C catalysts, and significantly reduces the production cost. Moreover, the electrocatalyst prepared by the present invention exhibits excellent hydrogen evolution activity in alkaline solution, achieving a hydrogen evolution overpotential as low as 13mV when the current density is 10mA / cm, and the catalytic efficiency is higher than that of the Pt / C catalyst. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Figure 1 XRD diagram of the electrocatalyst prepared in Example 1-2 of the present invention;
[0036] Figure 2 XRD diagram of the electrocatalyst prepared in Comparative Example 1-2 of the present invention;
[0037] Figure 3 This is a SEM image of the electrocatalyst prepared in Example 1 of the present invention;
[0038] Figure 4 TEM and energy spectrum of the electrocatalyst prepared in Example 1 of the present invention;
[0039] Figure 5 It is a comparison diagram of linear sweep voltammetric curves using the electrocatalyst prepared in Examples 1-2 of the present invention and the electrocatalyst prepared in Comparative Examples 3-4 as working electrodes;
[0040] Figure 6 It is a comparison diagram of linear sweep voltammetric curves using the electrocatalyst prepared in Comparative Examples 1-2 of the present invention as the working electrode;
[0041] Figure 7 This is a graph showing the stability test results of the electrocatalyst prepared in Example 1 of the present invention as the working electrode. DETAILED DESCRIPTION
[0042] The present invention is described in detail below in conjunction with the examples, so that the technical personnel of the relevant technical field can understand the present invention. It is necessary to point out here that the examples are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. The non-essential improvements and adjustments made to the present invention by the skilled person in the relevant field according to the above invention content should still belong to the scope of protection of the present invention. At the same time, the raw materials mentioned below that are not described in detail are all commercially available products; the process steps or preparation methods that are not mentioned in detail are all process steps or preparation methods known to those skilled in the art.
[0043] Example 1
[0044] A method for preparing a low-crystallinity MoO2 hollow nanosphere-loaded ruthenium atom heterostructure electrocatalyst (Ru / -AC-MoO2) comprises the following steps:
[0045] (1) 0.4 g of ammonium molybdate tetrahydrate was dissolved in 100 mL of water, dispersed evenly, and stirred at room temperature for 10 minutes; then, 600 mg of dopamine hydrochloride was added to the colorless solution, and the color of the solution directly changed to wine red; after continuous magnetic stirring for 30 minutes, 200 mL of anhydrous ethanol was added, and the color of the wine red solution changed to a uniform orange solution.
[0046] (2) After the orange solution was magnetically stirred for 5 minutes, about 2 mL (25-28 wt%) of aqueous ammonia was dropped into the solution, and the pH was adjusted to 10, so that the color of the solution changed to orange-red and Mo-polydopamine hollow nanospheres were formed; after continuing to magnetically stir for 15 minutes, 8 mL of RuCl3 aqueous solution (10 mg / mL) was added to the orange-red solution, and magnetic stirring was continued at 25°C for 8 hours to obtain ruthenium-loaded Mo-polydopamine hollow nanospheres; then the precipitate was collected by centrifugation, washed with deionized water and anhydrous ethanol 4 times, and then dried in an oven at 70°C for 12 hours.
[0047] (3) The dried solid powder was placed in a tube furnace under nitrogen atmosphere, heated to 550°C at a rate of 3°C / min for annealing for 3 hours, and then cooled to room temperature to obtain a highly crystalline electrocatalyst, which was recorded as Ru / -C-MoO2.
[0048] (4) 40 mg of highly crystalline Ru / -C-MoO2 catalyst powder was dissolved in 10 mL of deionized water and stirred evenly. Subsequently, 80 mg of NaBH4 was added to the solution, stirred at 1500 rpm at room temperature for 4 hours, washed with deionized water and anhydrous ethanol for 5 times, and finally dried in an oven at 70°C for 15 hours to obtain a low-crystallinity MoO2 hollow nanosphere-loaded ruthenium atom electrocatalyst, recorded as Ru / -AC-MoO2.
[0049] Example 2
[0050] A method for preparing an amorphous MoO2 hollow nanosphere loaded with ruthenium atoms heterostructure electrocatalyst (Ru / -A-MoO2) comprises the following steps:
[0051] (1) 0.8 g of ammonium molybdate tetrahydrate was dissolved in 200 mL of water, dispersed evenly, and stirred at room temperature for 10 minutes; then, 1.1 mg of dopamine hydrochloride was added to the colorless solution, and the color of the solution directly changed to wine red; after continuous magnetic stirring for 20 minutes, 500 mL of anhydrous ethanol was added, and the color of the wine red solution changed to a uniform orange solution.
[0052] (2) After the orange solution was magnetically stirred for 10 minutes, about 5 mL (25-28 wt%) of aqueous ammonia was dropped into the solution, and the pH was adjusted to 9.5, so that the color of the solution changed to orange-red and Mo-polydopamine hollow nanospheres were formed; after continuing to magnetically stir for 15 minutes, 16 mL of RuCl3 aqueous solution (10 mg / mL) was added to the orange-red solution, and magnetic stirring was continued at 25°C for 6 hours to obtain ruthenium-loaded Mo-polydopamine hollow nanospheres; then the precipitate was collected by centrifugation, washed with deionized water and anhydrous ethanol 5 times, and then dried in an oven at 80°C for 10 hours.
[0053] (3) The dried solid powder was placed in a tube furnace under nitrogen atmosphere, heated to 650°C at a rate of 3°C / min for annealing for 5 hours, and then cooled to room temperature to obtain a highly crystalline electrocatalyst, which was recorded as Ru / -C-MoO2.
[0054] (4) 40 mg of highly crystalline Ru / -C-MoO2 catalyst powder was dissolved in 10 mL of deionized water and stirred evenly. Subsequently, 160 mg of NaBH4 was added to the solution, stirred at 900 rpm at room temperature for 3 h, washed with deionized water and anhydrous ethanol for 5 times, and finally dried in an oven at 70 °C for 12 h to obtain an electrocatalyst of amorphous MoO2 hollow nanospheres loaded with ruthenium atoms, denoted as Ru / -A-MoO2.
[0055] Comparative Example 1
[0056] A method for preparing an amorphous MoO2 hollow nanosphere electrocatalyst (A-MoO2) comprises the following steps:
[0057] (1) Dissolve 0.5 g of ammonium molybdate tetrahydrate in 150 mL of water, disperse evenly, and stir at room temperature for 10 minutes; then, add 0.9 mg of dopamine hydrochloride to the colorless solution, and the solution color directly changes to wine red; after continuous magnetic stirring for 30 minutes, add 350 mL of anhydrous ethanol, and the wine red solution changes to a uniform orange solution.
[0058] (2) After the orange solution was magnetically stirred for 5 minutes, about 4.5 mL (25-28 wt%) of aqueous ammonia was dropped into the solution, and the pH was adjusted to 9.5, so that the color of the solution changed to orange-red and Mo-polydopamine hollow nanospheres were formed; after continuing the magnetic stirring for 20 minutes, Mo-polydopamine hollow nanospheres were obtained; then the precipitate was collected by centrifugation, washed with deionized water and anhydrous ethanol 5 times, and then dried in an oven at 80°C for 10 hours.
[0059] (3) The dried solid powder was placed in a tube furnace under nitrogen atmosphere, heated to 600°C at a rate of 3°C / min for annealing for 6 hours, and then cooled to room temperature to obtain a highly crystalline electrocatalyst, which was recorded as C-MoO2.
[0060] (4) 50 mg of highly crystalline C-MoO2 catalyst powder was dissolved in 10 mL of deionized water and stirred evenly. Subsequently, 240 mg of NaBH4 was added to the solution, stirred at 800 rpm at room temperature for 1.5 h, washed with deionized water and anhydrous ethanol for 5 times, and finally dried in an oven at 80 °C for 12 h to obtain an amorphous MoO2 hollow nanosphere electrocatalyst, denoted as A-MoO2.
[0061] Comparative Example 2
[0062] A method for preparing a low-crystallinity MoO2 hollow nanosphere electrocatalyst (AC-MoO2) comprises the following steps:
[0063] (1) 0.6 g of ammonium molybdate tetrahydrate was dissolved in 200 mL of water, dispersed evenly, and stirred at room temperature for 10 minutes; then, 1.3 mg of dopamine hydrochloride was added to the colorless solution, and the color of the solution directly changed to wine red; after continuous magnetic stirring for 30 minutes, 450 mL of anhydrous ethanol was added, and the color of the wine red solution changed to a uniform orange solution.
[0064] (2) After the orange solution was magnetically stirred for 5 minutes, about 6 mL (25-28 wt%) of aqueous ammonia was dropped into the solution, and the pH was adjusted to 9, so that the color of the solution changed to orange-red and Mo-polydopamine hollow nanospheres were formed; after continuing the magnetic stirring for 20 minutes, Mo-polydopamine hollow nanospheres were obtained; then the precipitate was collected by centrifugation, washed with deionized water and anhydrous ethanol 5 times, and then dried in an oven at 70°C for 15 hours.
[0065] (3) The dried solid powder was placed in a tube furnace under argon atmosphere, heated to 500°C at a rate of 2°C / min for annealing for 5 hours, and then cooled to room temperature to obtain a highly crystalline electrocatalyst, which was recorded as C-MoO2.
[0066] (4) 60 mg of highly crystalline C-MoO2 catalyst powder was dissolved in 15 mL of deionized water and stirred evenly. Then, 90 mg of NaBH4 was added to the solution, stirred at 700 rpm at room temperature for 2 h, washed with deionized water and anhydrous ethanol for 5 times, and finally dried in an oven at 70 °C for 12 h to obtain an electrocatalyst of amorphous MoO2 hollow nanospheres, denoted as AC-MoO2.
[0067] Comparative Example 3
[0068] A commercially available Pt / C catalyst (Pt loading of 20 wt%) was used as the electrocatalyst of Comparative Example 3.
[0069] Comparative Example 4
[0070] A commercially available Ru / C catalyst (Ru loading of 5 wt%) was used as the electrocatalyst of Comparative Example 4.
[0071] Performance Testing
[0072] 1. Composition analysis and microstructure
[0073] Figure 1 and Figure 2 The XRD patterns of Ru / -C-MoO2, Ru / -AC-MoO2, Ru / -A-MoO2, C-MoO2, AC-MoO2 and A-MoO2 prepared in Examples 1-2 of the present invention and Comparative Examples 1-2, respectively, wherein the horizontal axis 2-Theta represents the 2θ angle, and the vertical axis Intensity represents the intensity of the diffraction peak. Figure 1 and Figure 2 It can be seen that the untreated Ru / -C-MoO2 and C-MoO2 samples have strong XRD diffraction peaks, which indicates that they have high crystallinity. The crystallinity of MoO2 calculated by the crystallinity calculation formula is 89.3% and 89.2% respectively; the diffraction peak intensity can be reduced to different degrees by treating with different contents of NaBH4, thereby achieving different crystallinity regulation of the catalyst. Using the XRD pattern diffraction calculation formula, the crystallinity of MoO2 in Example 1 (Ru / -AC-MoO2) and Comparative Example 2 (AC-MoO2) is 19.6% and 22.8% respectively; while the MoO2 in Example 2 (Ru / -A-MoO2) and Comparative Example 1 (A-MoO2) is completely amorphous.
[0074] Figure 3 The microscopic morphology of the electrocatalyst of low-crystallinity MoO2 hollow nanospheres loaded with ruthenium atoms (Ru / -AC-MoO2) prepared in Example 1, wherein Figure 3 a and Figure 3 b is the SEM image at different magnifications. Figure 3 It can be found that the carrier of the electrocatalyst is a nano-microsphere with a hollow structure. This structure has more defects and is conducive to the full exposure of active sites, which is beneficial to improving the atomic utilization and further improving the catalytic performance of the electrocatalyst.
[0075] Figure 4 The high-resolution transmission electron microscopy (HR-TEM) image of the electrocatalyst of low-crystallinity MoO2 hollow nanospheres loaded with ruthenium atoms (Ru / -AC-MoO2) prepared in Example 1, wherein: Figure 4 a and Figure 4 b is the TEM image at different magnifications. Figure 4 b It can be seen that the catalyst contains amorphous MnO2 (Amorphous phase MnO2, the red circled part), crystalline MoO2 (Crystalline phase MnO2, the green circled part) and crystalline Ru (Crystalline phase Ru, the orange circled part); and both crystalline MoO2 and Ru have lamellar structures, and the lattice fringes can be clearly seen. After measurement, the spacing of MoO2 on the (011) crystal plane is 0.342nm, and the spacing of Ru on the (101) crystal plane is 0.208nm. Figure 4 d is Figure 4 c High-angle annular dark field scanning transmission electron microscopy image (HAADF) and the corresponding energy spectrum of the highlighted part. Figure 4 It is also confirmed that the MoO2 carrier exists mainly in amorphous form, while some crystalline MoO2 and Ru nanoparticles also exist, which is consistent with Figure 1 The XRD results are consistent with those of the previous study; the energy spectrum also confirms the existence and uniform distribution of Ru, Mo and O elements.
[0076] The contents of the electrocatalyst elements of Ru / -C-MoO2, Ru / -AC-MoO2 and Ru / -A-MoO2 prepared in Example 1 and Example 2 were tested by ICP-OES. The results are shown in Table 1.
[0077] Table 1:
[0078]
[0079] As can be seen from Table 1, the content of precious metal Ru in the electrocatalysts prepared in Examples 1-2 of the present invention is lower than the content of precious metal in the commercial electrocatalysts 20% Pt / C and 5% Ru / C of Comparative Examples 3-4.
[0080] 2. Electrochemical performance
[0081] 2 mg of the electrocatalysts prepared in Examples 1-2, Comparative Examples 1-2, and Comparative Examples 3-4 were dispersed in 1 mL of a Nafion / ethanol mixed solution and subjected to ultrasonic treatment for 30 minutes to obtain a catalyst suspension. The glassy carbon electrode was polished and dried naturally, and 10 μL of the electrocatalyst suspension was dropped onto an area of 0.07 cm 2 on a glassy carbon electrode and dried at room temperature.
[0082] All electrochemical tests were carried out at the Shanghai Chenhua electrochemical workstation. The experimental process is as follows:
[0083] The hydrogen evolution performance of the electrocatalysts prepared in Examples 1-2 and Comparative Examples 1-2 and the electrocatalysts of Comparative Examples 3-4 was tested in a standard three-electrode system, the electrolyte was 1 mol / L KOH, the graphite rod, the glassy carbon electrode and the mercury / mercury oxide electrode were used as the counter electrode, the working electrode and the reference electrode, respectively, and the HER activity as a single catalyst was tested by the LSV method. The scan rate of the LSV polarization curve was 2 mV / s, and the loading amount of the electrocatalyst was 0.285 mg / cm 2 , 100% IR compensation should be performed before LSV polarization curve test. The test results are as follows Figure 5-6 As shown. At 10mA / cm 2 The stability was tested by chronopotentiometry (ET) at a current density of Figure 7 shown.
[0084] Figure 5 The linear sweep voltammetry curves of the electrocatalysts prepared in Examples 1-2 of the present invention and the electrocatalysts prepared in Comparative Examples 3-4 as working electrodes are compared. Figure 5 The horizontal axis Potential represents voltage, and the vertical axis Current density represents current density. Figure 5 It can be seen that the low-crystallinity MoO2 hollow nanospheres loaded with ruthenium atoms prepared in Example 1 exhibit ultra-high electrocatalytic hydrogen evolution activity in 1 mol / L KOH electrolyte. The low-crystallinity Ru / -AC-MoO2 electrocatalyst prepared in Example 1 of the present invention exhibits ultra-high electrocatalytic hydrogen evolution activity at a current density of 10 mA / cm 2 The overpotential is only 13 mV, which is lower than 18 mV of the completely amorphous Ru / -A-MoO2 and 38 mV of the highly crystalline Ru / -C-MoO2 in Example 2; and also much lower than the overpotentials of 36 mV and 59 mV of the commercial electrocatalysts 20% Pt / C and 5% Ru / C in Comparative Examples 3 and 4. This indicates that the low-crystallinity Ru / -AC-MoO2 electrocatalyst has excellent electrocatalytic performance.
[0085] Figure 6 The linear scanning voltammetric curve comparison diagram of the electrocatalyst prepared in Comparative Examples 1-2 of the present invention as the working electrode is shown in FIG. Figure 6 It can be found that the low crystallinity AC-MoO2 hollow nanosphere electrocatalyst in Comparative Example 2 has a high current density of 10 mA / cm 2 The overpotential is only 421 mV, which is lower than the 530 mV of the highly crystalline C-MoO2 in Comparative Example 2 and the 469 mV of the completely amorphous A-MoO2 in Comparative Example 1. This shows that the catalytic activity of the catalyst can be effectively enhanced by controllable regulation of the crystallinity.
[0086] Figure 7The stability test result of the electrocatalyst prepared in Example 1 of the present invention as the working electrode is shown in FIG. Figure 7 The horizontal axis Time represents time, and the vertical axis Potential represents voltage. Figure 7 It can be seen that the low crystallinity Ru / -AC-MoO2 electrocatalyst prepared in Example 1 has a high conductivity at 10 mA / cm 2 The electrocatalyst can be stably operated for 100 h at a current density of 2.500 W with almost no decay, which indicates that the electrocatalyst has excellent stability.
[0087] For ordinary technicians in the technical field to which the present invention belongs, several simple deductions or substitutions can be made without departing from the concept of the present invention, without having to go through creative labor. Therefore, simple improvements made to the present invention by those skilled in the art based on the disclosure of the present invention should be within the protection scope of the present invention. The above embodiments are preferred embodiments of the present invention, and all processes similar to the present invention and equivalent changes made should belong to the protection scope of the present invention.
Claims
1. An electrocatalyst, characterized in that The invention comprises a carrier and ruthenium atoms, wherein the ruthenium atoms are loaded on the surface of the carrier and form a heterogeneous structure with the carrier; the carrier is a MoO2 hollow nanosphere with low crystallinity or amorphous state.
2. The electrocatalyst according to claim 1, characterized in that The crystallinity of the MoO2 is less than 23%.
3. The electrocatalyst according to claim 1, characterized in that The loading amount of the ruthenium atoms is less than 5 wt %.
4. A method for preparing an electrocatalyst according to any one of claims 1 to 3, characterized in that: The following steps are involved: (1) dissolving molybdate in water, adding dopamine hydrochloride and ethanol, mixing, and adjusting the pH value of the solution to be alkaline to obtain a mixed solution; (2) adding a ruthenium source to the mixed solution and mixing; After centrifugation and drying, the precursor powder is obtained; (3) annealing the precursor powder in an inert atmosphere to obtain high-crystallinity MoO2 hollow nanospheres loaded with ruthenium atoms, denoted as Ru / -C-MoO2; (4) The Ru / -C-MoO2 is dissolved in water, NaBH4 is added to adjust the crystallinity, and after centrifugation and drying, low-crystallinity or amorphous MoO2 hollow nanospheres loaded with ruthenium atoms are obtained, which are recorded as Ru / -AC-MoO2 or Ru / -A-MoO2.
5. The method for preparing an electrocatalyst according to claim 4, characterized in that: In step (1), the molybdate is selected from ammonium molybdate tetrahydrate and / or sodium molybdate; And / or, the molar ratio of Mo ions in the molybdate to dopamine hydrochloride is 1:(1-3); And / or, the pH value is 8.5-10.2; And / or, the volume ratio of water to ethanol is 1:(1-4).
6. The method for preparing an electrocatalyst according to claim 4, characterized in that: In step (2), the ruthenium source is selected from one of ruthenium dichloride, ruthenium trichloride, ruthenium oxalate, ruthenium nitrate, and ruthenium acetylacetonate; And / or, the usage relationship of the molybdate and the ruthenium source is 1:(5-40) in terms of the molar ratio of Ru to Mo.
7. The method for preparing an electrocatalyst according to claim 4, characterized in that: In step (3), the temperature regime of the annealing treatment is: heating to 450-850°C at a rate of 1-10°C / min for annealing for 2-6 hours, and then cooling to room temperature.
8. The method for preparing an electrocatalyst according to claim 4, characterized in that: In step (4), the mass ratio of Ru / -C-MoO2 to NaBH4 is 1:(1-4).
9. The method for preparing an electrocatalyst according to claim 4, characterized in that: In step (4), the drying temperature is 50-130° C.; and / or the drying time is 3-24 hours.
10. Use of the electrocatalyst according to any one of claims 1 to 3, or the electrocatalyst prepared by the preparation method according to any one of claims 4 to 9 in electrocatalytic hydrogen evolution.